Inland waters and their role in the carbon cycle of Alaska. Issue 5 (5th July 2017) - Stackpoole, Sarah M.; Butman, David E.; Clow, David W.; Verdin, Kristine L.; Gaglioti, Benjamin V.; Genet, Hélène; Striegl, Robert G.
Abstract: The magnitude of Alaska (AK) inland waters carbon (C) fluxes is likely to change in the future due to amplified climate warming impacts on the hydrology and biogeochemical processes in high latitude regions. Although current estimates of major aquatic C fluxes represent an essential baseline against which future change can be compared, a comprehensive assessment for AK has not yet been completed. To address this gap, we combined available data sets and applied consistent methodologies to estimate river lateral C export to the coast, river and lake carbon dioxide (CO2 ) and methane (CH4 ) emissions, and C burial in lakes for the six major hydrologic regions in the state. Estimated total aquatic C flux for AK was 41 Tg C/yr. Major components of this total flux, in Tg C/yr, were 18 for river lateral export, 17 for river CO2 emissions, and 8 for lake CO2 emissions. Lake C burial offset these fluxes by 2 Tg C/yr. River and lake CH4 emissions were 0.03 and 0.10 Tg C/yr, respectively. The Southeast and South central regions had the highest temperature, precipitation, terrestrial net primary productivity (NPP), and C yields (fluxes normalized to land area) were 77 and 42 g C·m −2 ·yr −1, respectively. Lake CO2 emissions represented over half of the total aquatic flux from the Southwest (37 g C·m −2 ·yr −1 ). The North Slope, Northwest, and Yukon regions had lesser yields (11, 15, and 17 g C·m 2 ·yr −1 ), but these estimates may be the most vulnerable to future climate change, because of the heightened sensitivity of arctic and boreal ecosystems to intensified warming. Total aquatic C yield for AK was 27 g C·m −2 ·yr −1, which represented 16% of the estimated terrestrial NPP. Freshwater ecosystems represent a significant conduit for C loss, and a more comprehensive view of land‐water‐atmosphere interactions is necessary to predict future climate change impacts on the Alaskan ecosystem C balance.